Determining grasp configurations using photometric stereo and the PRISM binocular - Ikeuchi, Katsushi; K Nishihara, H; K. P. Horn, Berthold; Sobalvarro, P; Nagata, S (The International Journal of Robotics Research, 1986)
This paper describes a system which locates and grasps parts from a pile. The system uses photometric stereo and binocu lar stereo as vision input tools. Photometric stereo is used to make surface ...